HIGH-TEMPERATURE GASIFICATION OF RDF WASTE AND MELTING OF FLY ASH OBTAINED FROM THE INCINERATION OF MUNICIPAL WASTE - Marián Lázár (Acta Polytechnica, 2015)
Objective of this paper is to describe innovative solutions of thermal processing of selected components of municipal waste (so-called RDF waste) using low-ionized depended plasma arc generated by a progressive and promising technology, which is plasma reactor. Its application can transform hazardous waste into inert waste while significantly reducing the volume of waste. Results given in this paper indicate experimentally achieved outputs with thermal disposal of RDF waste and ash from municipal waste.